Optimisation of the synthesis of second generation 1, 2, 4, 5 tetraoxane antimalarials. Issue 40 (6th October 2016) - O' Neill, Paul M.; Sabbani, Sunil; Nixon, Gemma L.; Schnaderbeck, Matthew; Roberts, Natalie L.; Shore, Emma R.; Riley, Christopher; Murphy, Ben; McGillan, Paul; Ward, Stephen A.; Davies, Jill; Amewu, Richard K.
Abstract: An efficient route to the synthesis of potent antimalarial aryloxy 1, 2, 4, 5-tetraoxanes is described that permits parallel synthesis for Structure–Activity Relationship (SAR) investigations. Brief details of the in vitro and in vivo antimalarial evaluation are included which enables identification of antimalarial leads for further development. Also described is an improved approach to the synthesis of a selected late-lead compound in just four or five synthetic steps from commercially available starting materials. Graphical abstract: